Roles of MicroRNA across Prenatal and Postnatal Periods - Floris, Ilaria; Kraft, Jamie; Altosaar, Illimar (Université d'Ottawa | University of Ottawa, 2016)
Communication between mother and offspring in mammals starts at implantation via the maternal-placental-fetal axis, and continues postpartum via milk targeted to the intestinal mucosa. MicroRNAs (miRNAs), short, noncoding single-stranded RNAs, of about 22 nucleotides in length, are actively involved in many developmental and physiological processes. Here we highlight the role of miRNA in the dynamic signaling that guides infant development, starting from implantation of conceptus and persisting through the prenatal and postnatal periods. miRNAs in body fluids, particularly in amniotic fluid, umbilical cord blood, and breast milk may offer new opportunities to investigate physiological and/or pathological molecular mechanisms that portend to open novel research avenues for the identification of noninvasive biomarkers.
Keywords: breast milk; maternal-offspring crosstalk; microRNA; noninvasive biomarkers; Amniotic Fluid; Animals; Biomarkers; Embryo Implantation; Female; Humans; MicroRNAs; Milk, Human; Pregnancy